2019
DOI: 10.1103/physrevc.99.024615
|View full text |Cite
|
Sign up to set email alerts
|

Insight into excitation energy and structure effects in fission from isotopic information in fission yields

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 51 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…These modes only exist at low energies or during spontaneous fission events. However, 30 years later, it is shown that these modes can also occur at high energies events (≈20 MeV) [22]. It had even been experimentally proven by Balabekyan et al, [23] nine years earlier.…”
Section: Introduction 1*mentioning
confidence: 94%
“…These modes only exist at low energies or during spontaneous fission events. However, 30 years later, it is shown that these modes can also occur at high energies events (≈20 MeV) [22]. It had even been experimentally proven by Balabekyan et al, [23] nine years earlier.…”
Section: Introduction 1*mentioning
confidence: 94%
“…Now new detailed experimental studies of staggering in fission-fragment charge distributions have become available for several fissioning nuclei and excitation energies, see Ref. [12] and references therein. Therefore we are now in a position to compare calculated and experimental global and local staggering quantities and their variation with excitation energy, element and isotope.…”
Section: Nascent Fragment Pairing Effectsmentioning
confidence: 99%
“…Ref. [7], with the heavy fragment being relatively neutron-rich and the lighter neutron-poor for fission of typical actinides, is reproduced. Though, the influence of shell effects in the vicinity of 132 Sn is weaker in theory as compared to the measurement.…”
Section: Post-scission Evaporationmentioning
confidence: 99%
“…Furthermore, unlike Ref. [16], we use an approximate formula [7] for the density of states of the deformed fragments, rather than the actual s.p. level densities with the shell effects.…”
Section: Post-scission Evaporationmentioning
confidence: 99%
See 1 more Smart Citation